Detection of Excipient-Excipient Interaction in Dry Powder Inhaler Formulation Prepared by Spray Drying - Aiesheh Gholizadeh-Hashjin; Hamed Hamishehkar; Farnaz Monajjemzadeh (Tabriz University of Medical Sciences, 2024)
Background: Dry powder inhalers (DPIs) are dosage forms that are used via the pulmonary route. Their formulations include two major parts; drug substance and carrier. For many years, DPIs have been made with lactose, a particularly popular carrier. Leucine has drawn more attention in recent years when it comes to DPI formulations made using the spray drying technique. Leucine was utilized in conjunction with carriers like lactose to enhance physicochemical and aerosolization properties. Method: In this investigation, when lactose and leucine were co-spray dried, the color of powders around the cyclone separators of the spray dryer turned brown while the produced powder in the collector was white. Both the white powder inside the collector and the brown powder around the cyclone separators were investigated by differential scanning calorimetry (DSC), Fourier transform-infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), x-ray diffraction (XRD), and liquid chromatography with tandem mass spectrometry (LC-MS-MS) to determine the identity of the degraded chemicals and to look for any potential interactions. Results: A new peak at 177 ºC in DSC analysis is a sign of interaction. Also, FT-IR analysis shows the new peak at 1627 cm-1 which is related to the carbonyl group. According to SEM and XRD analysis co spray dried leucine-lactose is amorphous. Obtained data from LC-MS analysis indicates the adduct compound of leucine-lactose that resulted from the Maillard reaction was detected in both white and brown powder. Also, the reaction proceeded to form n-formyl compound. Conclusion: There is a possibility of lactose and leucine incompatibility during DPIs manufacturing, especially in elevated temperature and humidity.